Raising and Sharing Revenues from Natural Resources : A Review of Country Practices - Brosio, Giorgio; Singh, Raju Jan (World Bank, Washington, DC, 2015)
Natural resources offer opportunities, but also bring challenges. They have generally been linked to a series of negative outcomes like economic decline, corruption, and conflict. Oil and minerals reserves, in particular, are often very spatially concentrated, and their discovery becomes a potential source of conflict between the governments, the people of the producing areas, and those of the rest of the country. But can this increased risk of conflict be prevented? Are there ways for the government to change this course of events? This paper tries to contribute to this discussion by looking at the international practices in raising and sharing natural resource revenues (NRR) among different levels of government. The study observes that sharing NRR with subnational governments of the producing areas is the prevailing practice worldwide. There is a rationale to compensate the subnational government of the producing areas for the negative environmental, social, and economic impact of production activities. Assignment to all - including the non-producing - subnational governments is less frequent, although it is increasingly used (particularly in Latin America). This option increases the number of stakeholders and gives them incentives to exert control. This is a relevant argument, particularly in countries with a weak capacity of public scrutiny of government activities. The volatility of revenue or the low absorption capacity of small government units may nevertheless create problems. Similarly, the allocation of NRR to individuals with direct transfers, a complement to the intergovernmental allocation rather than an alternative, can increase the welfare of citizens by increasing their scrutiny of NRR use by government.